2006
DOI: 10.1111/j.1365-2109.2005.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and combined microalgae on larval growth, development and survival of the commercial sea cucumber Holothuria spinifera Theel

Abstract: The results of the study on the suitable algal feed for the mass rearing of holothurian larvae through hatchery system are presented. Auricularia larvae. after 48 h of fertilization, obtained from induced spawning of Holoth~iria spinifera, were fed with different algae Isochrysis galbana, Nanodlloropsis snlinn, Pavlava lutheri. Tetmselmis chllii and Chaetoceros cnlcitrans as well as I. galbana+C. calcitrans to ascertain the effect of single and combined microalgal diet. The rate of feeding was 2 x lo4 cells la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 5 publications
2
33
2
Order By: Relevance
“…The second combined microalgae feeding treatment of T. chuii and C. calcitrans (T:C) showed larger larvae with bigger stomachs and higher survival rate than the larvae fed with single microalgae diets. Similar results of higher larvae growth and survival have been obtained for H. spinifera larvae fed with a combination of I. galbana and C. calcitrans (42.5 ± 0.7 μm/d and 72.6% ± 2.1) than that using microalgae in single diets ( I. galbana: 32.6 ± 0.8 μm/d and 67.8% ± 7.6 and C. calcitrans: 37 ± 0.8 μm/d and 51.3% ± 3.4) (Asha & Muthiah, ). In that study, single diets of I. galbana, C. calcitrans and T. chuii (among others) were used; the larvae fed with I. galbana during the first 5 days of experiment showed higher growth than those fed with C. calcitrans and T. chuii ; however, since D6 of the experiment, the larvae fed with C. calcitrans showed higher growth (Asha & Muthiah, ).…”
Section: Discussionsupporting
confidence: 77%
“…The second combined microalgae feeding treatment of T. chuii and C. calcitrans (T:C) showed larger larvae with bigger stomachs and higher survival rate than the larvae fed with single microalgae diets. Similar results of higher larvae growth and survival have been obtained for H. spinifera larvae fed with a combination of I. galbana and C. calcitrans (42.5 ± 0.7 μm/d and 72.6% ± 2.1) than that using microalgae in single diets ( I. galbana: 32.6 ± 0.8 μm/d and 67.8% ± 7.6 and C. calcitrans: 37 ± 0.8 μm/d and 51.3% ± 3.4) (Asha & Muthiah, ). In that study, single diets of I. galbana, C. calcitrans and T. chuii (among others) were used; the larvae fed with I. galbana during the first 5 days of experiment showed higher growth than those fed with C. calcitrans and T. chuii ; however, since D6 of the experiment, the larvae fed with C. calcitrans showed higher growth (Asha & Muthiah, ).…”
Section: Discussionsupporting
confidence: 77%
“…In general, in aquaculture industry, a binary compound diet is thought to provide a better balance of nutrients for aquatic animals than a single component diet (Coutteau, 1996;Southgate, 2003). Many studies have confirmed that sea cucumber fed with compound diets often exhibit higher survival and growth rates compared with those fed with single component diets (James et al, 1994;Ramofafia et al, 1995;Battaglene, 1999;Asha and Muthiah, 2006). Sea mud could provide certain nutrients or digestion regulators to sea cucumber, which included beneficial algae, decaying organic matter and mineral components which were vital to the metabolism of sea cucumber (Liu et al, 2009;Gong et al, 2012), avoiding the lack of nutritions in wet shrimp waste.…”
Section: Mixture Of Wet Shrimp Waste and Sea Mudmentioning
confidence: 90%
“…The early auricularia for the first 3 days can be fed at 2 Â 10 4 which can be slowly raised to 3 Â 10 4 in the mid-stage to 4 Â 10 4 in the later stage (Asha 2004). The larvae are found to survive well when fed by Isochrysis galbana but grow well when fed by Chaetoceros calcitrans; hence, a mixture of these two (1:1) is found to be an ideal feed for the auricularia larvae for 10 days (Asha and Muthiah 2006). By periodic assessment of larval growth rate, the feeding regime can be adjusted so that the auricularia larval survival rate can be improved even up to 80-90 %.…”
Section: Larval Feedingmentioning
confidence: 98%